Histopathologic Correlates of Temporal Diffusion Changes in a Rat Model of Cerebral Hypoxia/Ischemia - Miyasaka, Naoyuki; Nagaoka, Tsukasa; Kuroiwa, Toshihiko; Akimoto, Hideaki; Haku, Tomoko; Kubota, Toshiro; Aso, Takeshi (American Journal of Neuroradiology, 2000)
BACKGROUND AND PURPOSE: Although diffusion-weighted MR imaging is a powerful tool for evaluating brain ischemia, histopathologic correlates of temporal diffusion changes in cerebral hypoxia/ischemia have not been extensively examined. Diffusion-weighted MR imaging was used to evaluate the relationship between the time course of apparent diffusion coefficient (ADC) changes and the histopathologic findings in cerebral hypoxia/ischemia.METHODS: Thirty 3-week-old rats were subjected to either a 15-, 30-, or 60-minute hypoxic/ischemic insult (unilateral common carotid artery ligation and exposure to 8% oxygen), during and after which diffusion- and T2-weighted MR imaging was performed. Each animal was killed 48 hours or 6 hours after the insult, and fixed sections of the parietal cortex were examined by light microscopy. Ten other (control) rats were subjected to only unilateral common carotid artery ligation or hypoxia.RESULTS: The experimental rats showed three patterns of ADC change, depending on the duration of the hypoxic/ischemic insult: transient (15-minute), biphasic (15-, 30-, or 60-minute), and persistent (60-minute) ADC reduction patterns. The transient ADC reduction pattern (reduction during the insult and recovery after resuscitation) was associated with selective neuronal death. The biphasic and persistent ADC reduction patterns (transient recovery and no recovery after resuscitation, respectively) were associated with cerebral infarction.CONCLUSION: Different temporal patterns of ADC change are associated with different histopathologic findings. Although the clinical manifestations of these different histopathologic presentations are not yet defined, this study indicates that sequential diffusion studies are a potentially powerful tool in the evaluation of hypoxic/ischemic brain injury.